A positive psychology group intervention in Greek university students by the counseling center: Effectiveness of implementation - Kounenou, Kalliope; Kalamatianos, Antonios; Garipi, Aikaterini; Kourmousi, Ntina (Frontiers in Psychology, 2022)
Most of institutions in higher education have emphasized success in knowledge while overlooking students’ well-being. The present study aimed to examine the effectiveness of the implementation of a 5-week positive psychology group intervention to a sample of 69 students that were assigned to the intervention (N = 34) and the control group (N = 35). Pre and post measures were taken assessing positive and negative emotions, resilience, happiness, optimism, and self-esteem. In particular, Modified Differential Emotions Scale, Connor-Davidson Resilience Scale, Subjective Happiness Scale, Life Orientation Test-Revised, and Rosenberg Self-Esteem Scale were administered to the participants. A mixed measures design was employed with the condition experimental versus control group as the between-participants factor and time, namely, baseline versus post-intervention as the within-participants factor. Except for optimism, compared with students in the control group, students in the experimental group showed no significant differences at baseline and experienced a significant increase in positive emotions and resilience in the post-test. On the contrary, the control group demonstrated no significant difference at post-test. Additionally, the students of the intervention group reported significantly higher levels in all measures in comparison with the students of the control group, except resilience, at post-test. However, when the interaction of design and time was considered, the increase in positive emotions solely emerged as a significant result of the intervention. The implementation of a positive psychology group intervention program can be effective in helping students experiencing positive emotions. More research is needed in order to refine and improve the application of such a program in a university setting, in regard to long term intervention.